Correcting Confocal Acquisition to Optimize Imaging of Fluorescence Resonance Energy Transfer by Sensitized Emission - van Rheenen, Jacco (Biophysical Society, 2004)
Imaging of fluorescence resonance energy transfer (FRET) between suitable fluorophores is increasingly being used to study cellular processes with high spatiotemporal resolution. The genetically encoded Cyan (CFP) and Yellow (YFP) variants of Green Fluorescent Protein have become the most popular donor and acceptor pair in cell biology. FRET between these fluorophores can be imaged by detecting sensitized emission. This technique, for which CFP is excited and transfer is detected as emission of YFP, is sensitive, fast, and straightforward, provided that proper corrections are made. In this study, the detection of sensitized emission between CFP and YFP by confocal microscopy is optimized. It is shown that this FRET pair is best excited at 430 nm. We identify major sources of error and variability in confocal FRET acquisition including chromatic aberrations and instability of the excitation sources. We demonstrate that a novel correction algorithm that employs online corrective measurements yields reliable estimates of FRET efficiency, and it is also shown how the effect of other error sources can be minimized.